Fee‐for‐Value and wRVU‐Based Physician Productivity—An Emerging Paradox. Issue 3 (March 2015) - Abecassis, M.; Pearson, T.
<x xml:space="preserve">Abstract</x> Physician productivity and compensation face a paradox in the era of fee‐for‐value care delivery. See personal viewpoint by Abouljoud et al on page 601.